Word and spirit: a Kierkegaardian critique of the modern age - Hall, Ronald L. (The Indiana series in the philosophy of religion, 1993)
By means of a Kierkegaardian critique of postmodernism, Ronald L. Hall argues that the postmodernist flirtation with Kierkegaard ignores the existential import of his thought. Word and Spirit offers a novel interpretation of Kierkegaard's conception of the self, according to which spirit is essentially linked to the speech act. In an extended interpretation of Kierkegaard's Either/Or, Hall uses insights from Austin, Wittgenstein, Polanyi, and Poteat to fill out and explicate Kierkegaard's views in the context of modern language philosophy. The enriched concept of the speech act represented by the Hebrew idea of dahhar frames Hall's critique of irony, romanticism, Don Giovanni, Faust, the demonic, music, and, ultimately, postmodernism in a Kierkegaardian mode. The result of the modern suspicion of speech, Hall concludes, is a demonic, musical spiritlessness